Avaliação do Sistema Permanente de Avaliação da Educação Básica do Ceará: um olhar do professor sobre a influência do SPAECE-ALFA no currículo do 2º Ano do Ensino Fundamental - Gomes, Kátia Cilene Rodrigues (2025)
External assessments are exams that are administered to schools to assess the actions of education systems, with the aim of seeking a quality coefficient through student performance. In this context, the priorities in school actions to prepare students for good results require teachers to take responsibility for their performance. This study seeks to evaluate, from the perspective of teachers at a public school in Fortaleza, Ceará, the influences of Spaece-Alfa on the curriculum of the 2nd year of Elementary School, which is the general objective of this research. Spaece-Alfa is a large-scale assessment that is part of the Permanent System for the Assessment of Basic Education in Ceará, applied in the 2nd year of Elementary School, in all municipalities in the state of Ceará. This assessment is the result of the emergence of the Literacy Program at the Right Age (PAIC) in 2007, in the state of Ceará. It is the instrument that the State uses to verify the level of proficiency in reading and writing of children in this grade. In addition to the general objective, the specific objectives are: 1) To study the Permanent System of Basic Education Assessment (Spaece), as a public policy, together with Spaece-Alfa; 2) To identify curricular actions and practices experienced by 2nd grade elementary school teachers, focusing on Spaece-Alfa, in a school in the city of Fortaleza; 3) To analyze the implications of Spaece-Alfa in the 2nd grade elementary school curriculum, in a school in the city of Fortaleza, from the teachers' perspective. The evaluative perspective of the research is based on the work of Rodrigues (2008), in an in-depth assessment. The methodology chosen to approach the problem is qualitative and, in terms of meeting the objectives, exploratory. A bibliographical survey was conducted in the works of Saviani (2016), Arroyo (2013), Afonso (2007), Ball (2014), Gonçalves (2003) among others, and a documentary survey in laws, decrees and ordinances that instituted the public policy under study and important curricular documents in Brazilian, state and municipal education of Fortaleza. A field research was included, carried out in a public school in the capital of Ceará through semi-structured interviews with three teachers from the school where the investigation took place, using a questionnaire. Data analysis had a content analysis perspective according to Bardin (2014). As a result, it was verified the influence that the Spaece-Alfa test has on the actions of teachers in the planning, evaluation and development of content, adopting teaching practices so that the 2nd grade student of Elementary School is increasingly able to answer the questions of said external evaluation. All this with the aim of improving the school's performance in the results of children's reading proficiency